A case of mitral papillary muscle rupture due to blunt chest trauma - Bakiler, Ali Rahmi; Aydoğdu, S Ayvaz; Erişen, Seda; Yenigün, Ayşe; Atay, Yüksel (The Turkish Journal of Pediatrics, 2011)
Mitral regurgitation due to papillary muscle rupture after blunt chest trauma is uncommon. Sudden onset severe mitral regurgitation may lead to death due to heart failure if surgical repair is delayed. A previously healthy 12-year-old girl underwent splenectomy and chest tube insertion for pneumothorax after a traffic accident in a vehicle 15 days before. She was discharged from the hospital after a nine-day follow-up. She was presented to our hospital due to respiratory distress. On physical examination, an apical holosystolic murmur radiating to the axillary region was recognized. Transthoracic echocardiogram showed severe mitral regurgitation with freely moving posterior mitral chordae and prolapse of the posterior mitral valve leaflet. She received reimplantation of the complete ruptured posteromedial papillary muscle of the mitral valve. Her medical condition improved after the operation. On the postoperative echocardiogram, the left ventricular systolic function was normal with no mitral regurgitation.